QCL fabrication, characterisation and its application - Lee, Desiree Sze Pin (2019)
Mid-infrared Quantum Cascade Lasers (QCL) have been rapidly developing and heavy research has been done on it. They are becoming more popular for a variety of applications. An overview of QCL is presented in this paper including the fabrication of it. The basic features and properties are introduced first. The characterisation processes as well as its operation are also described. The applications of QCL is further explored. Comprehensive testing results are analysed and discussed, yielding valuable information about QCL.